Optimum engine cooling system by redesigning a water cooling pump impeller - 555166 Alias Mohd. Noor; Mardani Ali Sera; Srithar Rajoo; International Conference on Advances In Strategic Technologies (ICAST 2000) (2nd :2000 : Selangor) (Skudai : Universiti Teknologi Malaysia, 2000)
20